The Evaluation of Three Companies of General Motors, Procter & Gamble, and Colgate-Palmolive - Lu, Yuhao (Transactions on Economics, Business and Management Research, 2024)
The article focuses on the risk-return analysis of companies from different industries, including Car Manufacturing and FMCG (Fast Moving Consumer Goods). By using risk-return analysis in various corporates, investors could enhance their understandings on market dynamics, identifying investment opportunities, spreading risks in order to make more rational investment choices. This analysis helps investors to improve their returns and reduce risks. This research collects various indices, including risk targets (market betas, debt and current ratios, investment ratings), profitability measures (total asset turnover, profit margin, return on assets, return on equity), and market ratios (PB ratio, PE ratio, PEG ratio, dividend yield, current stock price, and 200-day moving average). The findings indicate why different types of investors, including value, PEG, index, valuation, and momentum investors might choose companies like General Motors, Procter & Gamble, and Colgate-Palmolive. Finally, the paper aims to enhance understanding of industry dynamics, corporate behavior, and provide investment advice. Besides, this could be useful to serve as a valuable resource for novice investors and future research discussions.